Dynamical evolution of anisotropic response of type-II Weyl semimetal TaIrTe₄ under ultrafast photoexcitation - Zhuo, Xiao (2021)
Layered type-II Weyl semimetals, such as WTe₂, MoTe₂, and TaIrTe₄ have been demonstrated as a supreme photodetection material with topologically enhanced responsivity and specific sensitivity to the orbital angular momentum of light. Toward future device applications with high performance and ultrafast response, it is necessary to understand the dynamical processes of hot carriers and transient electronic properties of these materials under photoexcitation. In this work, mid-infrared ultrafast spectroscopy is performed to study the dynamical evolution of the anisotropic response of TaIrTe₄. The dynamical relaxation of photoexcited carriers exhibits three exponential decay components relating to optical/acoustic phonon cooling and subsequent heat transfer to the substrate. The ultrafast transient dynamics imply that TaIrTe₄ is an ideal material candidate for ultrafast optoelectronic applications, especially in the long-wavelength region. The angle-resolved measurement of transient reflection reveals that the reflectivity becomes less anisotropic in the quasi-equilibrium state, indicating a reduction in the anisotropy of dynamical conductivity in presence of photoexcited hot carriers. The results are indispensable in material engineering for polarization-sensitive optoelectronics and high field electronics.